Melatonin biosynthesis and regulation in reproduction - Zhong, Jingjing; Lu, Zhiyong; Zhou, Zhi; Ma, Ning; Li, YeJuan; Hu, JiaJia; Wan, Bangbei; Lu, Weiying (Frontiers in Endocrinology, 2025)
Melatonin, a neuroendocrine hormone widely present in animals, is a derivative of tryptophan secreted by the pineal gland. This hormone regulates animal circadian rhythms and can affect reproductive performance in many ways; for example, melatonin levels change in response to sunshine duration changes, which can inhibit or promote reproductive performance. In juvenile animals, melatonin inhibits estrus, whereas in mature animals, it promotes estrus. Melatonin regulates animal reproductive activities mainly through the hypothalamus–pituitary–gonad axis and through membrane binding receptor (MT1 and MT2) interactions. It effectively removes cellular free radicals that have strong antioxidant effects and can directly act on the reproductive system and even early embryos by improving tissue and cell anti-inflammatory and antioxidant functions, improving animal reproductive performance. Although modern human fertility is no longer affected by seasonal reproduction, the relationship between melatonin and human reproduction remains unclear. Melatonin is important for improving mitochondrial function, reducing free radical damage, and inducing oocyte maturation, which can improve the fertilization rate, promote embryo development, and positively affect in vitro fertilization and embryo transfer. Here, we describe the biosynthesis and regulation of melatonin and its secretion, the physiological function of melatonin, and its effects on animal reproductive performance and assisted reproduction.